Mutation in LEMD3 (Man1) Associated with Osteopoikilosis and Late-Onset Generalized Morphea: A New Buschke-Ollendorf Syndrome Variant. (13th June 2016) - Korman, Benjamin; Wei, Jun; Laumann, Anne; Ferguson, Polly; Varga, John
Abstract : Introduction . Buschke-Ollendorf syndrome (BOS) is an uncommon syndrome characterized by osteopoikilosis and other bone abnormalities, accompanied by skin lesions, most frequently connective tissue nevi. BOS is caused by mutations in the LEMD3 gene, which encodes the inner nuclear membrane protein Man1. We describe a unique case of osteopoikilosis associated with late-onset localized scleroderma and familial LEMD3 mutations. Case Report . A 72-year-old woman presented with adult-onset diffuse morphea and bullous skin lesions. Evaluation revealed multiple hyperostotic lesions (osteopoikilosis) suggestive of BOS. DNA sequencing identified a previously undescribed nonsense mutation (Trp621X) in the LEMD3 gene encoding Man1. Two additional family members were found to have osteopoikilosis and carry the same LEMD3 mutation. Conclusions and Relevance . We report a unique familial LEMD3 mutation in an individual with osteopoikilosis and late-onset morphea. We propose that this constellation represents a novel syndromic variant of BOS.